Ocorrências e distribuição de bactérias resistentes a metais pesados em sedimentos da Baía do Araça, São Sebastião (SP) - Zampieri, Bruna Del Busso [UNESP] (2015)
One of the major ecological concerns, nowadays, refers to anthropogenic environmental impact caused by heavy metals release in diverses natural environments, since these pollutants are extremely persistent and pervasive. At high concentration heavy metals are extremely toxic to bacteria, being able to influence the density and metabolic activity. However, bacteria are capable to develop heavy metal resistance mechanisms in the environment, being important in bioremediation of contaminated areas. Therefore, the purpose of the study was to assess the occurrence and distribution of heavy metal resistance bacteria in Araça Bay, São Sebastião - SP. 12% of the isolated bacteria were sensitive to all metals. It was observed that the highest percentage of resistant strains were in the subtidal region that is closest to the São Sebastião channel, where port activity are concentrated. Bacterial isolates were more resistant to Cr, followed by Zn, Cd and Cu. Regarding the minimum inhibitory concentration, a lower number of strains resisted levels greater than 200 mg L-1 for Cd. While for Cr, 36% of the strains grew even at a concentration of 3200 mg L-1. For Zn, Cu, few strains (4% and 2%, respectively) grew in higher concentrations like 1600 mg L-1 and none could withstand the highest concentration (3200 mg L-1). Bacillus sp was the most isolated genera and may be a dominant genre in heavy metal contaminated areas, especially species Bacillus pumilus and Bacillus cereus. Staphylococcus sp, Planococcus maritmus and Vibrio aginoliticus were also isolated and have potential for use in bioremediation of contaminated sites